Binder Jetting 3D Printing of Titanium Aluminides Based Materials: A Feasibility Study - Yadav, Pinku; Fu, Zongwen; Knorr, Moritz; Travitzky, Nahum (Advanced Engineering Materials, 2020)
This study offers the ability to fabricate nearly dense titanium aluminides-based structures using a hybrid method that encompasses binder jetting 3D printing (3DP) of Ti–6Al–4V followed by pressureless ex situ infiltration with Al. Microstructure characterization and phase analysis are performed by scanning electron microscopy equipped with energy dispersive spectroscopy and X-ray diffraction, respectively. The microstructure of the samples fabricated by means of pressureless ex situ infiltration at different temperatures and with various durations is studied and discussed. The nearly dense titanium aluminides-based composites shows a Young's modulus of ≈145 GPa, a compressive strength of ≈1.4 GPa and a bending strength of ≈483 MPa. To demonstrate technological capability of this hybrid approach, complex near-net-shaped objects are fabricated.
CRIS-Team Scopus Importer:2020-06-09
Keywords: 3D printing; metal-matrix-composites; titanium 6–4; titanium aluminides